Religion and modernity in India - Bandyopadhyay, Sekhar; Parasher-Sen, Aloka (Oxford University Press, 2017)
Through a series of case studies taken from everyday experiences of people following a variety of religions, this book interrogates the supposed epistemological dualism between modernity and religion in India. Through a study of oral and textual traditions, examining the perspectives of women and other marginal social and regional groups, as well as the diaspora, it presents dynamically interacting textures of society-historically and in our contemporary times-engaging with modernity in divergent ways.